Express 2x^2 +8x +7 in the form A(x+B)^2 + C, where A, B and C are constants

2x2+8x+7=2(x2+4)+7=2((x+2)2-4)+7=2(x+2)2-8+7=2(x+2)2-1A=2, B=2, C=-1

Answered by Matilda C. Maths tutor

7715 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the differential of y(x)=(5x*Cos(3x))^2


Solve 4cos(2x )+ 2sin(2x) = 1 given -90° < x < 90°. Write 4cos(2x )+ 2sin(2x) in the form Rcos(2x - a), where R and a are constants.


Differentiate the following: 4x^3 + sin(x^2)


Find the solution(s) of 3(x^2)-6x+2=0


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences